Heart rate variability reflects training load and psychophysiological status in young elite gymnasts - Sartor, F.; Vailati, E.; Valsecchi, V.; Vailati, F.; La Torre, A. (The Journal of Strength and Conditioning Research, 2013)
In gymnastics, monitoring of the training load and assessment of the psychophysiological status of elite athletes is important for training planning and to avoid overtraining, consequently reducing the risk of injures. The aim of this study was to examine whether heart rate variability (HRV) is a valuable tool to determine training load and psychophysiological status in young elite gymnasts. Six young male elite gymnasts took part in a 10-week observational study. During this period, beat-to-beat heart rate intervals were measured every training day in weeks 1, 3, 5, 7, and 9. Balance, agility, upper limb maximal strength, lower limb explosive, and elastic power were monitored during weeks 2, 4, 6, 8, and 10. Training load of each training session of all 10 weeks was assessed by session rating of perceived exertion (RPE) and psychophysiological status by Foster`s index. Morning supine HRV (HF% and LF%/HF%) correlated with the training load of the previous day (r = 0.232, r = -0.279, p < 0.05 ). Morning supine to sitting HRV difference (mean R wave to R wave interval (RR), mean heart rate, HF%, SD1) correlated with session RPE of the previous day (r = -0.320, r = 0.301, p < 0.01; r = 0.265, r = -0.270, p < 0.05) but not with Foster`s index. Training day/reference day HRV difference (mean RR, SD1) showed the best correlations with session RPE of the previous day (r = -0.384, r = -0.332, p < 0.01) and Foster`s index (r = -0.227, r = -0.260, p < 0.05). In conclusion, HRV, and in particular training day/reference day mean RR difference or SD1 difference, could be useful in monitoring training load and psychophysiological status in young male elite gymnasts.